Pengaruh Motivasi Investasi, Pemahaman Investasi Dan Minat Investasi Pada Mahasiswa - Perangin Angin, Aldian Syahputra; Raj, Saran; Silitonga, Pirhot; Pandiangan, Yeni Harlianti; Siallagan, Hamonangan; Sipayung, Rizki Christian (Universitas Pahlawan Tuanku Tambusai, 2023)
Indonesian people, especially students, are still very consumptive, uphold a hedonic lifestyle and forget to invest in preparation for the future amid the rapid development of the investment world. This study aims to determine the effect of investment motivation and understanding of investment on students' investment intentions. This research uses quantitative methods. The number of correspondents in this study amounted to 66 students who were taken by purposive sampling technique. Data was collected by distributing questionnaires via the Google form. This study uses the method of linear regression analysis and multiple regression with the help of the SPSS program. To analyze the effect of investment motivation (X1) and investment understanding (X2) on investment interest (Y) the t-test is used. The test results show that the influence of investment motivation and investment understanding has a significant influence on investment interest in students Medan/Universitas HKBP Nommensen with a significance value of 0.041 for investment motivation and 0.000 for investment understanding. Where the value is still less than 0.05. This study also found that investment motivation and investment understanding had an influence on student investment interest by 82.4%